CELIA dan gelas-gelas di kepalanya / Lugina WC...[et al] ; penyunting, Addin, Muhajjah, Misni ; ilustrator, Ferdika - Lugina WC; Addin; Muhajjah; Misni; Ferdika (Diva Press, 2016)
255 hlm. : ilus. ; 20 cm